Nabda’ bi Nuqtah: An ADDIE-Based Academic Writing Incubation Model - Andrian, Riko; Salmas, Ahmad Nurul Huda; Yul, Widiya (Study Program of Arabic Language Teaching, 2026)
This study aims to develop and evaluate the program’s effectiveness in improving students’ academic writing skills and publication productivity. This study employed a Research and Development (R&D) method using the ADDIE framework: analysis, design, development, implementation, and evaluation. It was conducted from July to August 2025 in the Graduate School of UIN SUSKA Riau. The participants were six active students from semesters I–III, selected through purposive sampling based on commitment to academic writing, absence of prior publications, and diverse academic backgrounds. Data were collected through observations, interviews, and document analysis, and analyzed using qualitative and quantitative approaches. The result is a structured scientific incubation program supported by mentoring modules, assessment tools, and publication guidelines. Limited implementation showed significant effectiveness in enhancing writing motivation, improving manuscript quality, and increasing publication output. This study recommends broader implementation to strengthen academic culture and postgraduate publication capacity.